Influences of corporate governance and corporate strategy on performance of finance companies in Malaysia - Kallamu, Basiru Salisu (2014)
This study presents evidence on the influence of corporate governance mechanisms and corporate strategy on performance of finance companies listed on Bursa Malaysia. The sample includes all the finance companies listed on the main market of Bursa Malaysia from the period 1992 to 1996 (pre MCCG period) and from 2007 to 2011 representing period after the Malaysian Code on Corporate Governance (MCCG, 2000) was issued. The study aims to determine whether ownership structure, board subcommittees’ attributes and diversification have influence on performance of finance companies in both the period before and after the MCCG was issued.The results indicate a statistically significant relationship between corporate governance and corporate strategy, and firm performance. Firstly, indirect director ownership has significant influence on firm performance in the post MCCG period. This supports agency theory and means that ownership by directors helps align the interest of inside and outside stakeholders’ thereby reducing expropriation and enhancing intermediary role and firm performance. The presence of institutional ownership is found to be negatively related with firm performance in the pre MCCG period. Their inactive participation in the monitoring activities of the companies can be related to their holdings of diversified investment portfolio to reduce their risk exposure and protect their investment return. The presence of high proportion of independent directors on the board enhances firm value when executive board members hold shares in the firm indicating the effectiveness of their monitoring role in aligning inside owners’ interests with minority shareholders. When executive board members own shares in the firm, the presence of independent chair is negatively related with firm performance, which could imply redundancy in monitoring role since there is already shareholders on the board to monitor the decision making process. Secondly, the results indicate that composition of audit committee (AC) is positive and significant while interlock of directors on AC and nomination committee (NC) is negatively related with performance in the post MCCG period. This supports agency theory and means that having independent directors on AC enhance monitoring role of the AC thereby enhancing performance. The result also means that interlock of directors on subcommittees can affect their ability to monitor firms effectively. In the pre MCCG period, directors’ expertise and experience is negative and positively related with performance respectively. This means that expertise and experience of the AC members does not enhance performance due to the less complex nature of the activities of the financial institutions in the period before MCCG. Thirdly, composition of risk management committee (RMC) is negatively related with profitability while independent committee chair positively enhances profitability. This means that having independent directors on the RMC does not add value to the firms due to the complex nature of operations of financial institutions and due to lack of technical knowledge and inside information by independent directors about firms’ risk activities. In addition, executive experience of directors is positive while executive membership of RMC is negatively related with performance. This means that directors experience positively influence their monitoring of risk while having executive directors on RMC hinders effective monitoring of the risks in firms. Fourthly, independent remuneration committee (RC) chair is significant but negatively related with performance meaning that independent RC chair does not enhance firm profitability. Fifthly, directors’ expertise and executive membership of NC are significant but positively and negatively related with performance respectively. This means that expert directors on NC enhance profitability by improving the process of selecting competent directors to the board while negative relationship means that having executive directors on NC affects director selection which affects board monitoring and firm performance. Sixthly, diversification is negative while formation of separate risk committee is positively related with performance respectively. This implies that diversification does not necessarily enhance profitability while separating RMC from AC helps enhance firm performance by enhancing the monitoring of risks inherent in the intermediary role of finance firms and their operations. The results also indicate significant difference in corporate governance of finance firms between the period before and after MCCG was issued. The findings contribute to literature and our understanding of the benefits of director ownership, independent directors on board and its subcommittees, independent board and committee chair, expertise and experience of the directors on subcommittees, diversification and separate RMC on the intermediary role of financial institutions by showing an association between corporate governance mechanisms, corporate strategy and firm performance. Management, board of companies and regulators may use the findings to make appropriate choices about governance mechanisms and strategy that enhance firms’ intermediary role in order to improve performance.